Creating rainmakers : - Harding, Ford (John Wiley & Sons, 2006)
Every manager of a professional firm realizes that generating leads and landing new clients are critical components of any successful business venture. But transforming accountants, architects, attorneys, consultants, engineers, and other professionals into client-generators is not always easy to do. Divided into two comprehensive parts-The Rainmaker Model and The Elements of Rainmaking-Creating Rainmakers outlines all the steps you should take to turn your professional staff into a powerful team of sales winners. Filled with in-depth insight and practical advice, this book will show you how to: Generate leads; Build a strong network of contacts; Master a variety of sales techniques; Develop capable successors to current rainmakers; And much more.